Environmental Health Risk Analysis Due to Carbon Monoxide (CO) Exposure among Traders on Jalan H. Agus Salim, Bataraguru, Baubau City - Siti Nurmaya; Ramadhan Tosepu; Asramid Yasin (International Journal Of Health Science, 2025)
Karya Nugraha Market is one of the central shopping areas of Baubau City residents located on H. Agus Salim Street, Bataraguru Village, Baubau City. Every day the area is crowded with all types of vehicles. One of the emissions from motor vehicles is carbon monoxide (CO). This study aims to analyze carbon monoxide (CO) exposure to traders selling on H. Agus Salim Street, Karya Nugraha Market, Baubau City. Air quality measurements were carried out for three days (Saturday, Sunday and Monday) at 3 measurement points (point 1, the entrance area of Karya Nugraha Market, point 2, the parking area, and point 3, the vegetable seller area), within 8 hours, namely in the morning (06:00-09:00), noon (12:00-14:00) and in the afternoon (16:00-18:00). This research method uses descriptive observation. The sample used was 89 people . The respondent data collection technique was purposive sampling with the Environmental Health Risk Analysis (ARKL) method. For carbon monoxide (CO) concentration sampling, the AS8700A Carbon Monoxide Meter was used . The results of the research that has been carried out the concentration value on Saturday the highest value is in the afternoon of 27.207 μg / m 3, on Sunday of 47.613 μg / m 3 and on Tuesday the highest value is 36.276 μg / m 3. Of the 3 three sample points in the morning, afternoon and evening have an RQ value ≤ 1 so it can be said to be not at risk . Thus, it is hoped that the Baubau City Environmental Service will routinely monitor the spread of pollutant concentrations, especially carbon monoxide (CO) on Jalan H. Agus Salim, Karya Nugraha Market, Baubau City to support air pollution control.